Homoarginine, cardiovascular risk, and mortality - März, Winfried; Meinitzer, Andreas; Drechsler, Christiane; Pilz, Stefan; Krane, Vera; Kleber, Marcus E.; Fischer, Joachim E.; Winkelmann, Bernhard R.; Böhm, Bernhard O.; Ritz, Eberhard; Wanner, Christoph (Circulation, 2010)
Homoarginine is an amino acid derivative that may increase nitric oxide availability and enhance endothelial function. The effect of the level of homoarginine on cardiovascular outcome and mortality is unknown.
Gesehen am 02.05.2023